Factor XIIa inhibition by Infestin-4: in vitro mode of action and in vivo antithrombotic benefit - Xu, Yiming; Cai, Tian-Quan; Castriota, Gino; Zhou, Yuchen; Hoos, Lizbeth; Jochnowitz, Nina; Loewrigkeit, Christopher; Cook, John A.; Wickham, Alexandra; Metzger, Joseph M.; Ogletree, Martin L.; Seiffert, Dietmar A.; Chen, Zhu (Thrombosis and Haemostasis, 2014)
Coagulation factor XII (FXII) plays a central role in initiating the intrinsic cascade of blood coagulation. Purified recombinant Human Albumin- tagged Infestin-4 (rHA-Infestin-4) is a recently described FXIIa inhibitor that displayed strong anticoagulant activity without compromising haemostasis in several animal models. We pursued detailed invitro characterisation of rHA-Infestin-4 and demonstrated that it is a competitive inhibitor of FXIIa with slow on and off rate constants for binding (kon=5x105 M-1s-1, koff=6x10–4 s-1), it can block FXIIa activation of its physiological substrates (plasma prekallikrein and FXI), and it can inhibit ellagic acid-triggered thrombin generation in plasma. Potency and selectivity profiling in enzyme assays suggest that rHAInfestin- 4 is indeed highly potent on FXIIa (IC50=0.3 ± 0.06, 1.5 ± 0.06, 1.2 ± 0.09 nM, for human, rat, and rabbit FXIIa, respectively) with at least >100-fold selectivity against factors IIa, Xa, IXa, XIa, VIIa, and plasma kallikrein in all three species. rHA-Infestin-4 dose-dependently and markedly reduced clot weight in the arteriovenous shunt thrombosis model in rats and rabbits, accompanied with minimal increase in cuticle bleeding times in either species. rHA-Infestin-4 treatment at 5 mg/kg in rabbit resulted in a 13% reduction in ex vivo FXa activity, demonstrating a modest off-target effect. In summary, our findings confirmed and extended previous reports that inhibition of FXIIa by rHA-Infestin-4 can produce strong antithrombotic efficacy while preserving haemostasis. Our comprehensive selectivity profiling, mode of action, and kinetic studies of rHA-Infestin-4 reveal limitations of this molecule and offer new perspectives on any potential effort of discovering novel FXIIa inhibitors.
Keywords: Factor XIIa; Infestin-4; coagulation; thrombosis; bleeding